A textual analysis of western thought and civilization from the perspectives of scholars of the 20th century / Azlan Khalili Shamsuddin - Shamsuddin, Azlan Khalili (2008)
This research dissertation aims to analyze viewpoints of scholars of the 201h century concerning Western thought and civilization. In particular ten scholars have been chosen to analyse their thinking and responses to Western civilization namely: i) Seyyed Hossein Nasr ii) Sayyid Abul A'la Al Maududi iii) Sayyid Qutb iv) Abul Hasan Ali Nadawi v) Muhammad Asad vi) Maiyam Jameelah vii) Syed Muhammad Naquib al Attas and viii) Muhammad Urner Chapra. The research will explore the views of the above-mentioned scholars regarding various aspects of Western thought and civilization. Aspects of Western thought and civilization that will be discussed are as follows: i) Secularism and ii) Spiritual, moral and ethical issues. The methodology of research in undertaking this Ph.D. programme is only one that is through a textual analysis of relevant literatures available as related to the research. An analysis of these literatures as related to the research subject had been done by referring to the books written by the afore-mentioned scholars. Generally it can be said that these scholars do not view Western thought and civilization favourably and they have contributed greatly to understanding the history and roots of Western thought and civilization, as well as offered positive criticism of them. Since all of them can be regarded as scholars of Islam, their criticism of Western thought and civilization were mostly viewed from the Islamic perspective.